Buildings with persona: Towards effective building-occupant communication. (October 2017) - Khashe, Saba; Lucas, Gale; Becerik-Gerber, Burcin; Gratch, Jonathan
Abstract: Occupant behavior is one of the most significant contributors to building energy consumption. Employing communication systems to enable buildings to interact with their occupants and influence the way they behave could significantly reduce energy consumption. We investigated the effectiveness of different delivery styles (i.e., avatar, voice, and text), as well as the impact of communicator's persona (i.e., building facility manager and building itself) and gender (i.e., male and female) on occupants' compliance with pro-environmental requests. The results showed that avatar is more effective than voice and voice is more effective than text on promoting compliance with persuasive pro-environmental requests. In addition, results showed greater compliance with requests made by the persona of a building facility manager than the persona of the building itself. Finally, participants were more likely to comply with the female communicator than the male communicator. Accordingly, this new interaction between buildings and their occupants could impact human behavior. Highlights: Avatars were found to be more effective than voice at evoking compliance. Avatars and voice were more effective than text at prompting compliance. Participants comply with requests from female communicators more than males. Compliance was greater when personified as the building facility manager rather than the building.